Створення високоефективного радіаційно-конвективного рекуператора для печі вторинної плавки алюмінію - Воробйов, Микита Валерійович; Згурський, Володимир Олександрович; Прокоф'єв, Олексій Сергійович; Губатюк, Руслан Сергійович (Національний технічний університет "Харківський політехнічний інститут", 2021)
Запропонована високоефективна конструкція радіаційно-конвективного рекуператора із вторинними випромінювачами, в якому за рахунок раціонального розташування поверхонь нагріву, а також за рахунок встановлення вторинних випромінювачів в димових каналах, забезпечується збільшення теплосприйняття, яке передається вторинному теплоносію – повітрю. На основі проведених теоретичних досліджень, інженерних розрахунків та CFD – моделювання визначено характеристики роботи рекуператора для його встановлення на печі вторинної плавки алюмінію. Основними перевагами запропонованої конструкції є висока теплогідравлічна ефективність, компактність і низька металоємність, зручність розміщення на печі і відсутність необхідності в розміщенні в окремих димоходах.

The high efficient design of the radiation-convective recuperator with secondary emitters have been proposed, in which due to the rational arrangement of heating surfaces, as well as due to the installation of secondary emitters in flues, an increase in heat perception is transmitted to the secondary heat carrier – preheating air. High efficiency of air preheating is provided by two-stage heating: 1st stage of heating – the internal air ring channel with bilateral heating which is washed by combustion products from the parties of the central cylindrical and peripheral ring channels of combustion products; 2nd stage of heating – the external air ring channel in which unilateral heating by products of combustion from the peripheral ring channel of products of combustion is organized. Inner and outer annular air ducts (tanks), interconnected by bypass pipes. To increase the efficiency of heat transfer in the considered recuperator in the central channel of combustion products is placed emitter, which consisting of intersecting radial plates, and in the annular channel of combustion products are placed auxiliary emitters, which made in the form of flat radial edges. These emitters provide an increasing in total heat flux to the walls of the channels of the recuperator. On the basis of the conducted theoretical researches, engineering calculations and CFD – modelling the characteristics of operation of the recuperator for its installation on the furnace of secondary smelting of aluminium are defined. The main advantages of the new design of recuperator are high thermo-hydraulic efficiency, compactness and low metal consumption, ease of installation on the furnace and no need for placement in separate chimneys. It is established that the recuperator provides air heating ta,ex ~ 400 °C at an acceptable aerodynamic drag (pressure drop) on the air track (∆pa ~ 1000 Pa). Appropriate design documentation has been developed for the manufacture of the recuperator, which is installed on a pilot furnace of secondary aluminium smelting by California Die Casting (USA).
Development of highly efficient radiation-convective recuperator for furnace of secondary aluminum melting
Keywords: вторинна плавка алюмінію; вторинні випромінювачі; промислові печі; радіаційноконвективний рекуператор; утилізація теплоти; air preheating; industrial furnaces; heat recovery